2023
DOI: 10.1039/d2cp03666e
|View full text |Cite
|
Sign up to set email alerts
|

Combined computational and experimental study about the incorporation of phosphorus into the structure of graphene oxide

Abstract: Phosphorus-containing graphene-based hybrids are materials with outstanding properties for applications in the field of electrochemical devices. In this work, an easy route to produce phosphorus-graphene oxide hybrid materials is described,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 97 publications
2
11
0
Order By: Relevance
“…Another recent study investigated incorporation of phosphoric acid during synthesis of graphene oxide and showed that phosphate can bind to graphene oxide both by hydrogen bonding to graphene oxide's functional groups and by covalent bonding under harsh synthesis conditions. 28 This study supports functionalized graphene nanomaterials as good candidates for phosphate binding. Therefore, in this work, we investigated pristine graphene and engineered graphenes such as curved graphene, graphene with vacancies, and oxygenated graphene containing epoxide and hydroxyl groups as sensor materials for the detection of phosphate through density functional theory (DFT) calculations.…”
Section: ■ Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Another recent study investigated incorporation of phosphoric acid during synthesis of graphene oxide and showed that phosphate can bind to graphene oxide both by hydrogen bonding to graphene oxide's functional groups and by covalent bonding under harsh synthesis conditions. 28 This study supports functionalized graphene nanomaterials as good candidates for phosphate binding. Therefore, in this work, we investigated pristine graphene and engineered graphenes such as curved graphene, graphene with vacancies, and oxygenated graphene containing epoxide and hydroxyl groups as sensor materials for the detection of phosphate through density functional theory (DFT) calculations.…”
Section: ■ Introductionsupporting
confidence: 68%
“…In a recent study, graphene-transition metal composites were used as adsorbents to remove phosphate from water; however, this approach relies on expensive and potentially toxic transition metals, therefore a cheaper functionalization such as oxygen, defects, or curvature control would be preferable. Another recent study investigated incorporation of phosphoric acid during synthesis of graphene oxide and showed that phosphate can bind to graphene oxide both by hydrogen bonding to graphene oxide’s functional groups and by covalent bonding under harsh synthesis conditions . This study supports functionalized graphene nanomaterials as good candidates for phosphate binding.…”
Section: Introductionmentioning
confidence: 57%
“…Additionally, less abundant and weaker signals corresponding to other oxygenated functional groups, such as lactol (101 ppm), carbonyl (192 ppm), and carboxyl (167 ppm) groups, are also detected. The other dominant resonance in these spectra occurs at a chemical shift around 132 ppm, corresponding to nuclei in hexagonal rings formed by -hybridized carbon atoms, which are a common feature of both graphene oxides and graphite oxides [ 28 , 38 ]. The relative intensities of the resonances due to the oxygen-containing functional groups (mainly epoxy and hydroxyl groups) are higher in the case of the GOP sample, which agrees with previous reports indicating the high oxidation degree of samples prepared by the Tour method and its variations [ 27 , 28 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The GOP sheets were synthesized following a modified Tour method [ 27 ]. The amounts of H 2 SO 4 and H 3 PO 4 used in the reaction were changed in comparison with the route originally proposed by Tour et al [ 28 ], while keeping the total acid volume at 140 mL, using 50 mL of H 2 SO 4 and 90 mL of H 3 PO 4 . For the graphite oxidation reaction, about 1.0 g of the graphitic precursor was added to the H 2 SO 4 + H 3 PO 4 mixture, followed by the slow addition of 6.0 g of KMnO 4 .…”
Section: Methodsmentioning
confidence: 99%
“…In fact, the socalled Marcano-Tour method [22] involves a modification of the original graphite oxidation method proposed by Hummers and Offeman [23], replacing H 2 SO 4 with a 9:1 (v/v ratio) H 2 SO 4 /H 3 PO 4 mixture. Previous reports have shown that GO samples prepared by the Marcano-Tour method exhibit a high degree of oxidation, resulting in general in O/C atomic ratios larger than those reached by using the Hummers method [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%